Index Number Biases During Price Liberalization - Osband, Kent (IMF Working Papers; Working Paper, 1991)
When a formerly centrally-planned economy frees prices and allows or compels producers to respond to market signals, conventional measures tend to severely overstate short-run output decline and inflation. In part the overstatement stems from neglect of private sector activity, or from belated recognition of inflation previously disguised as quality improvements. Even when individual prices and outputs are correctly measured, however, shifts in relative prices consequent to price decontrol create a serious aggregation problem. Moreover, the standard indices ignore the deflationary trends in black markets. Superior growth and inflation indices are devised using a combination of official and black market prices.